Parametric Building Envelopes Rationalized in Terms of Their Solar Performance in a Temperate Climate - Jacek Abramczyk; Wiesław Bielak (Energies)
The article presents a method of shaping unconventional building envelopes characterized by their effective solar performance in a temperate climate. An analysis related to the impact of geometric shape on the solar direct radiation falling on building envelopes was presented in terms of polyhedral forms. It was based on interdisciplinary issues located in the fields of solar radiation, unconventional forms of buildings, numerical simulations, and artificial neural networks. The elaborated method’s algorithm was employed to describe the relationships between the envelope systems and the amount of the radiation falling on these systems, identified during the performed simulations. Two novel parametric models were defined to execute the simulations. The first was an initial geometric model defined by a number of arbitrary independent variables. The second was defined by one dependent variable representing the quantity of the solar radiation falling on each envelope. The analysis carried out showed that the invented trapezoidal forms of envelopes allowed for better control of the incident solar radiation in relation to the forms generated with other methods. The invented trapezoidal forms of envelopes can increase the amount of their direct solar irradiation up to 63%, compared to prior pyramidal forms. Although the climatic loads used were related to Strzyżów characterized by the geographical coordinates 49.9 N and 21.9 E and located in Central Europe, it was possible to adapt the method to other meteorological boundary conditions by changing the values of the defined parameters. The resultant parametric solar model can be employed to search for many diversified discrete solar envelopes of buildings and rational arrangements of their external planes so that the direct solar radiation falling on these envelopes can be increased during cold periods and restricted during hot summer periods of the year.